Optimization of Laccase Production using White Rot Fungi and Agricultural Wastes in Solid-State Fermentation - Hendro Risdianto; Elis Sofianti; Sri Harjati Suhardi; Tjandra Setiadi (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
Abstract. Laccase has been produced in a solid-state fermentation (SSF) process using white rot fungi and various lignocellulose-based substrates. The white rot fungi used were Marasmius sp., Trametes hirsuta, Trametes versicolor and Phanerochaete crysosporium. The solid substrates employed in this research were collected from agricultural waste, specifically empty fruit bunches (EFB), rice straw, corncobs and rice husks. The objective of this research was to determine the most promising fungus, the best solid substrate and the optimal conditions for the production of laccase. The results showed that Marasmius sp. on all solid substrates displayed a higher laccase activity than that of any other strain of white rot fungi. Marasmius sp. and a solid substrate of rice straw demonstrated the highest laccase activity of 1116.11 U/L on day 10. Three significant factors, i.e. pH, temperature and yeast extract concentration, were studied by the response surface method on laccase production using Marasmius sp. and rice straw. The optimized conditions were a pH, temperature and yeast extract concentration of 4.9, 31ºC and 0.36 g/L, respectively. The fermentation of Marasmius sp. in SSF on agricultural waste shows a great potential for the production of laccase.